Advancing Fucoxanthin Production from Microalgae: A Bibliometric Analysis of Research Trends and Innovations - Azimatun Nur, Muhamad Maulana; Dewi, Resti Nurmala; Hadi, Faizah; Widayati, Tunjung Wahyu; Jaya, Danang; Tjun, Nita Afroskina; Nisya, Alinda Fitriani (International Journal of Marine Engineering Innovation and Research, 2025)
Fucoxanthin has attracted significant public attention due to its extensive bioactive properties, including antioxidant, anti-inflammatory, and anti-obesity effects. This study conducts a bibliometric analysis to assess research trends, key contributors, and scientific progress in fucoxanthin studies. By utilizing data from prominent scientific databases, various bibliometric indicators, such as publication output, citation patterns, and collaborative networks, were analyzed. The analysis reveals a consistent rise in research publications over the past two decades, with significant contributions from countries like Germany, Japan, and China. Additionally, the study identifies leading institutions and influential authors who have significantly impacted the field. The results highlight the expanding interest in fucoxanthin's potential applications in pharmaceuticals, functional foods, and nutraceuticals. Furthermore, the study sheds light on collaborative efforts between academic institutions and industries that drive innovation and commercialization. This comprehensive evaluation not only provides an understanding of the current research landscape but also identifies future directions for scientific exploration and technological advancements. The findings serve as a valuable resource for researchers, policymakers, and industry stakeholders to make informed decisions and foster innovation in the utilization of fucoxanthin for human health and sustainability.